Scaling Relations for the Cosmological “Constant” in Five-Dimensional Relativity - Paul S. Wesson; James M. Overduin (Advances in High Energy Physics)
When the cosmological “constant” is derived from modern five-dimensional relativity, exact solutions imply that for small systems it scales in proportion to the square of the mass. However, a duality transformation implies that for large systems it scales as the inverse square of the mass.